LOVE, LOSS, AND LONGING ACROSS POETIC TRADITIONS: A TEXTUAL COMPARISON BETWEEN WESTERN AND EASTERN POETRY - Hikmah Wardani; Iskandar Sulaiman; Fitriyani Fitriyani (State University of Makassar, 2026)
This study analyzes the representation of love, loss, and longing in Edgar Allan Poe's